Peningkatan Keterampilan Deteksi Dini Dan Manajemen Awal Kegawatdaruratan Ibu Hamil - Alfaina Wahyuni; Sri Nabawiyati Nurul Makiyah; Sri Sumaryani (Jurnal Empathy Pengabdian Kepada Masyarakat, 2022)
Background: The mortality rate in Indonesia, particularly in Bantul, remains quite high. Recognizing signs and symptoms of emergency cases in pregnant women and their families and midwives' preparedness as the community's spearhead of health services is essential in dealing with emergency cases of pregnant women. Methods: The lecture method, question and answer, and practical skills for midwives are used. The achievement of the activity is evaluated by analyzing the knowledge of pregnant women and midwives both before and after the activity. The T-test was used to analyze the data. Results: The results obtained are quite satisfactory. It was demonstrated by the high level of interest displayed by the participants during the question and answer session. Quantitative results from statistical tests revealed a significant increase in knowledge in pregnant women (53.90 21.97 vs. 89.47 9.7; P 0.000) and local health centre midwives (72.60 7.04 vs. 79.46 7.21; P 0.001). Conclusion: There was an increase in pregnant women's knowledge of recognizing the signs and dangers of pregnancy and midwives' knowledge and skills in terms of early detection and emergency treatment of pregnant women at community health centres.